Pemanfaatan Energi Cahaya untuk Sistem Penyiraman Otomatis Berbasis Internet of Things (IoT) di SMA Negeri 2 Lembang - Dulhamin Arif; Shandi Noris; Erfin Nurfalah; Ahmad Subeki; Rina Hidayati Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2025)
Watering plants is an important activity that cannot be ignored in order to maintain sufficient air intake for optimal growth. Manual watering methods, which are commonly carried out according to a schedule, are often inefficient because they require significant allocation of time and energy. Improper watering techniques are one of the risks of plant growth factor failure, where unmaintained soil moisture can cause plants to wilt and die. This study aims to develop an automatic irrigation system based on the Internet of Things (IoT) that utilizes light energy as its power source, with the aim of being able to save time, lighten human work, and at the same time optimize the use of energy resources. This system is designed to monitor soil conditions in real-time and regulate watering automatically, supported by a sustainable light energy source. The results of this study indicate that the automatic watering system based on the Internet of Things (IoT) developed and powered by light energy is able to overcome the problem of plant drought effectively, while saving time and lightening human work in watering activities.